Potential Protective Role of Melatonin in Benign Mammary Cells Reprogrammed by Extracellular Vesicles from Malignant Cells - Procópio de Oliveira, Caroline; Frigieri, Barbara Maria [UNESP]; Fukumasu, Heidge; Chuffa, Luiz Gustavo de Almeida [UNESP]; Novais, Adriana Alonso; Zuccari, Debora Aparecida Pires de Campos [UNESP] (MDPI, 2023)
(1) Background: Mammary neoplasms in female dogs share many similarities with the same tumor class in humans, rendering these animals a valuable preclinical model for studying novel therapies against breast cancer. The intricate role of extracellular vesicles (EVs), particularly exosomes, in breast carcinogenesis, by transferring specific proteins to recipient cells within the tumor microenvironment, underscores their significance. Melatonin, a hormone recognized for its antitumor effects, adds another layer of intrigue. (2) Methods: EVs obtained from the plasma of dogs diagnosed with mammary tumors were co cultivated with the benign epithelial lineage E-20 using DMEM. The experiment comprised four 24 h treatment groups: control, EVs, melatonin, and EVs + melatonin. A series of assays were conducted, including colony formation, proliferation, and cellular migration assessments. Furthermore, we conducted colony formation, proliferation, and cellular migration assays. We performed immunohistochemistry for proteins of the mTOR pathway, including mTOR and AKT. (3) Results: Exosomes alone significantly increased proliferation, migration, and colony formation rates and, upregulated the expression of mTOR and AKT proteins. However, when melatonin was added, a protective effect was observed. (4) Conclusions: These findings contributed to the use of melatonin to modulate EV-mediated signaling in the clinical veterinary oncology of mammary tumors.
Keywords: breast cancer; extracellular vesicles (EVs); melatonin